Determinación de la concentración de mercurio en la cuenca media del río Moche (Caserío Santa Rosa - Laredo). Noviembre 2019 - Mantilla Vásquez, Liliana (2020)
The purpose of this thesis is to “ Determination of mercury concentration in the middle basin of the Moche River (Santa Rosa - Laredo farmhouse). November 2019 ” These waters serve to supply the majority of the populations, among these to the places of Otuzco, Julcan, Agallpampa, Quiruvilca, Motil, Poroto, Menocucho, Santa Rosa and others that use the water without any treatment for agriculture. The sample of water that is the study material were taken in January in four different sectors: Poroto, Pedregal, Menocucho and Santa Rosa. The values found were: (0.00008 mg / L) in sample 1, (0.0001 mg / L) in sample 2, (0.0002 in sample 3) and (0.0002 in sample 4) presenting 2 of them above the values allowed by Decree-Supreme-N ° -015-2018-MINAM of the Ministry of Environment; According to the analysis carried out, it is observed that these waters receive the tailings of mining companies during the course of the Moche river in the department of liberty, predominantly in the community of Quiruvilca, which is where the largest tailings are produced. There is also little activity contamination of the Salpo mines and the Moche mines, which are almost inoperative